73Hemoglobin a1c levels and the risk of ischemic stroke and mortality in individuals with diabetes mellitus and atrial fibrillation. (18th June 2020) - Kezerle, L; Tsadok, M A; Akriv, A; Feldman, B; Leventer-Roberts, M; Ohana, R; Haim, M
Abstract: Funding Acknowledgements: Pfizer Israel Background: Diabetes mellitus (DM) is associated with increased risk of embolic complications in non-valvular atrial fibrillation (NVAF). Whether the risk of stroke in AF patients remains the same among the wide spectrum of disease is yet to be determined. Aim: Among individuals with AF and DM, to assess the incidence rates and risk of ischemic stroke and mortality by baseline HbA1C levels. Methods: We conducted a prospective, historical cohort study using the Clalit Health Services (CHS) electronic medical records database. The study population included all CHS members ≥ 21 years old, with a first diagnosis of NVAF between January 1, 2010 to December 31, 2016 and a minimal follow-up period of 1 year. Among those patients identified as diabetics, we compared three groups of patients according to HBA1C levels at the time of AF diagnosis: <7.0%, between 7-9% and ≥ 9%. Results: A total of 44, 451 cases were identified. The median age was 75 years (IQR 65-83) and 52.5% were women. During a mean follow up of 38 months, the incidence of stroke per 100 person-years in the three study groups was: 1.9 in patients with HBA1C <7%, 2.37 in the intermediary group and 2.72 in those with HBA1C >9%. In both univariate and multivariate analyses, higher levels of HBA1C were associated with an increased risk of stroke compared with a dose-dependent response when compared to individuals with HBA1C <7% (Adjusted Hazard Ratio (AHR) = 1.32 {95% CI 1.12-1.55}for levels between 7-9% and AHR 1.64 {95% CI 1.28-2.09}) even after adjusting for CHA2DS2-VASC individual risk factors and use of oral anti-coagulants. The risk for overall mortality did not differ significantly between groups, with a slight elevation in the HBA1C >9% group after adjusted analysis {aHR = 1.17 (1.07- 1.28)} Conclusion: In this observational cohort of patients with incident newly diagnosed nonvalvular atrial fibrillation, HBA1C levels were associated with an increased risk of stroke in a dose-dependent manner even after accounting for other recognized risk factors for stroke in this population.